Planning Of Beam Structure In The Diamond Hospital Building In Gebang Cirebon West Java - Syarifuddin, Syarifuddin; Muhtadin, Dodi; Syahgian, Agi; Sumarman, Sumarman (Indonesian Journal of Multidisciplinary Science, 2025)
This scientific work focuses on the beam structure of the hospital building designed with consideration for safety and strength. This hospital building has 4 levels with a height of 16m, a length of 60m, and a width of 40m, and is located in Gebang, Cirebon Regency, West Java. This structure is designed using SRPMK and is in accordance with safety standards based on SNI 1726:2019, 1727:2020, SNI 2847:2019. Structural analysis uses the ETABS 19 application, and the results show that the building structure can withstand several loading components. Thus, the design of the beam structure of this hospital building has met the applicable planning standards.